Beyond the Gendered Stereotypes: The Conflict of Motherhood in Dollie Radford’s Poetry - Hadeel Azhar (Journal of Umm Al-Qura University for Language Sciences and Literature, 2021)
This article sheds light on motherhood as a theme which – to my knowledge – has not been thoroughly explored to date in Dollie Radford’s volumes of poetry published in the last decades of the nineteenth century. It positions Radford’s depiction of the theme within Victorian conventions, and simultaneously in line with the radical meanings embraced by her contemporary women poets, including Christina Rossetti, Alice Meynell and Augusta Webster. In doing so, the article approaches the representation of motherhood at different levels, thereby eschewing a fixed reading of the selected poems. It offers an insight into Radford’s conflict as a mother who wishes to enlighten both her children and the future generation away from the prevailing doctrines. Thus, the argument presented herein adds to the existing body of knowledge on Radford and challenges the gendered readings imposed upon her poems by Victorian reviewers.